Inovasi Mesin Pemarut Kelapa Berbasis Teknologi Tepat Guna dalam Mendukung Peningkatan Kapasitas Produksi UMKM - Muhammad Ramadhani Suryolaksono (Dharma: Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to design and implement a coconut grating machine to enhance the production capacity of a coconut-grating small and medium-sized enterprise (SME) in Dukuhwaluh, Banyumas Regency. The main challenge faced by the partner was low productivity due to the use of conventional grating methods, which required relatively long processing times and offered limited production capacity. The implementation methods included an initial survey and field observation, machine design and fabrication, functional testing, and assistance during the machine adoption process. The machine was designed using a 200 W electric motor coupled with a belt and pulley transmission system to ensure stable, safe, and user-friendly operation. Testing results showed that the machine achieved an average grating capacity of 20 kg/h, representing an improvement over the previous method, which could only process approximately 16 kg/h. The implementation of the machine increased SME productivity by 25% and reduced the grating processing time by 20%. The machine's electricity consumption was recorded at 0.22 kWh per hour of operation, making it economically feasible for small-scale enterprises. From an economic perspective, the use of the machine is estimated to increase business revenue by 20%. Overall, the implementation of this appropriate technology-based coconut grating machine has proven effective in improving production efficiency and effectiveness, increasing production capacity, and generating positive economic impacts for the partner SME. The results demonstrate that the adoption of appropriate technology can serve as an effective solution for enhancing the competitiveness and sustainability of micro-enterprises in the Dukuhwaluh area